Pengembangan Jobsheet Robotika Line Follower Robot berbasis Mikrokontroler Arduino UNO - Fikry Fauzi; Iwanto Irwanto; Endi Permata (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
Abstract— This research is based on the fact that in the Department of Industrial Electronics Engineering at SMKN 4 Serang City there is no learning media on robotic system controller subjects. On that basis, a line follower robot learning media was designed which is expected to overcome this problem. The learning media designed is in the form of a learning worksheet that contains 6 (six) jobs including how to assemble components, forward motion commands, backward motion, left turn motion, right turn motion and combination motion. The development of this jobsheet learning media uses a 4D research model which consists of 4 research steps, namely define, design, develop and disseminate. The purpose of this study was to create media and a line follower robot learning worksheet, then also to determine the feasibility level of the media. Based on the feasibility test conducted on media experts, material experts and user tests covering several aspects such as the feasibility of content, appearance and language, it was found that the line follower robot learning jobsheet was